Coagulation monitoring correlation with heparin dose in pediatric extracorporeal life support. (November 2017) - Moynihan, Katie; Johnson, Kerry; Straney, Lahn; Stocker, Christian; Anderson, Ben; Venugopal, Prem; Roy, John
Objectives: Extracorporeal Life Support (ECLS) risks thrombotic and hemorrhagic complications. Optimal anti-coagulation monitoring is controversial. We compared coagulation tests evaluating the heparin effect in pediatric ECLS. Methods: A retrospective study of children (<18yrs) undergoing ECLS over 12 months in a tertiary pediatric intensive care unit (PICU). Variables included anti-Factor Xa activity (anti-Xa), activated partial thromboplastin time (aPTT), activated clotting time (ACT) and thromboelastogram (TEG ® 6s) parameters: ratio and delta reaction (R) times (the ratio and difference, respectively, between R times in kaolin assays with and without heparinase). Test results were correlated with unfractionated heparin infusion rate (IU/kg/hr) at the time of sampling. Mean test results of each ECLS run were evaluated according to the presence/absence of complications. Results: Thirty-two ECLS runs (31 patients) generated 695 data-points for correlation. PICU mortality was 22% and the thrombotic complication rate was 66%. The proportion of variation in coagulation test results explained by heparin dose was 13.3% for anti-Xa, 11.9% for ratio R time, and 9.9% for delta R time, compared with <1% for ACT and aPTT. Incorporating individual variation, age and antithrombin activity in a model with heparin dose explained less than 50% of the variation in test results. Correlation varied according to age, day of ECLS run and between individuals, with parallel dose-response lines noted between patients. Significantly lower mean anti-Xa was observed in PICU non-survivors and runs with thrombosis. Conclusion: Lower anti-Xa was observed in ECLS runs with complications. Although absolute results from anti-Xa and TEG6 ® s showed the best correlation with heparin dose, a large proportion of variation in results was unexplained by heparin, while dose response was similar between individuals. Population pharmacokinetic/pharmacodynamic modelling is required, as well as prospective trials to delineate the superior means of adjusting heparin therapy to prevent adverse clinical outcomes.